2016
DOI: 10.17265/2159-5275/2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical Buckling of Drill Strings in Cylindrical Cavities of Inclined Bore-Holes

Abstract: Notwithstanding the fact that the problem of drill string buckling (Eulerian instability) inside the cylindrical cavity of an inclined bore-hole attracts attention of many specialists, it is far from completion. This peculiarity can be explained by the complexity of its mathematic model which is described by singularly perturbed equations. Their solutions (eigen modes) have the shapes of boundary effects or buckles (harmonic wavelets) localized in zones of the bore-hole that are not specified in advance. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Thus, authors [4] examined the loss of stability of drill string of smooth tubes in the sloping well and demonstrated that the numerical results for the case when inclination angle of the well is equal to the angle of friction coincide with those obtained analytically. Researchers [5] studied the impact of rotation speed on the deflection of drill string and the magnitude of reaction in the zone of contact with the well wall.…”
Section: Literature Review and Problem Statementmentioning
confidence: 71%
See 1 more Smart Citation
“…Thus, authors [4] examined the loss of stability of drill string of smooth tubes in the sloping well and demonstrated that the numerical results for the case when inclination angle of the well is equal to the angle of friction coincide with those obtained analytically. Researchers [5] studied the impact of rotation speed on the deflection of drill string and the magnitude of reaction in the zone of contact with the well wall.…”
Section: Literature Review and Problem Statementmentioning
confidence: 71%
“…That is, research [1,2,[4][5][6][7][8][9][10] is mostly devoted to studying the behavior of drill string, mantled from smooth pipes, under loading.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…This paper offers a new asymptotic treatment for the classical problem of (static) lateral buckling of a long DS that remains in contact with the wall of an inclined straight borehole. The weight of the DS as well as the frictional forces experienced by this configuration are both accounted for, with the mathematical model being formulated as a boundary eigenvalue value problem for an angular displacement [29,36]. Our key results correspond to the non-dimensional three-term asymptotic formulae ( 29), (34), and (37), which capture the dependence of the first two lowest eigenvalues on all the relevant physical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A succinct account of the key differential equations and assumptions used in the rest of this paper is presented in this section. The mathematical model we are planning to explore was discussed at length in Gulyayev et al [29] or Musa et al [36], to which interested readers are referred for full details and derivations. Here, we will be content in just highlighting those aspects that are required in order to make the paper reasonably self-contained.…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation